O perfil do consumidor e a percepção das estratégias de marketing em três mercados de proximidades agroecológicos no estado de Minas Gerais - Araújo, Heliene Macedo de (2017)
The objective of this dissertation was to identify the marketing strategies used in selected agroecological proximity markets associated with the perception and the profile of the consumers of these sites, and the specific objectives (1) to compare the strategies of marketing mix and environmental marketing that are currently adopted , At the Terra Viva Fair in the city of Belo Horizonte / MG; At the Agroecological Fair Raízes do Campo in Jaboticatubas / MG; And, in the Mercadinho "Tá caindo fulô" in the district of Santana do Riacho / MG; (2) identify the main barriers faced in such proximity markets to market agro-ecological products from the perspective of consumers; And (3) identify the behavior and profile the consumer of agroecological products in relation to the marketing mix and environmental marketing variables in the proximity markets surveyed. For the theoretical reference the concepts of agroecology, solidary economy, organic agriculture, marketing strategies, Environmental Marketing, Social and 3.0 were discussed. The survey method used was the Survey. The technique of data collection used was documentary research, direct observation and questionnaire with primary data collection. For the analysis of the results we used descriptive statistical analysis, comparative quantitative analysis, multivariate cluster analysis and cluster / local segmentation, and chi-square tests to verify the dependence between variables. With the results it was possible to identify that the markets studied have specific marketing strategies, without, however, having prior planning for their executions. Environmental and Social Marketing is perceived as transversal in all actions of the sites and Marketing 3.0 was observed in the three sites. Regarding consumers' understanding of agroecological products, it has been suggested that not all consumers of the sites surveyed know everything about the agroecological product and not everyone is completely unaware of the products. With the multivariate analysis of Cluster it was possible to identify 2 clusters being called "Consumers closer to agroecological knowledge" and "Sustainable Consumers and less close to agroecological knowledge. In addition, in order to contribute to the elaboration of marketing strategies for each group, the segmentation of the consumers considering site / cluster was carried out, thus allowing to identify the profile of the consumers in relation to the variables of marketing mix and environmental marketing. From this research it was evidenced that the study of marketing strategies, consumer behavior and the use of quantitative analyzes (such as cluster analysis and market segmentation) has the potential to identify the real perceptions of consumers in relation to markets And assertively define the limitations of the sites and which strategies are most appropriate to both meet the needs and desires of the consumers, achieve the goals of the organizations with regard to social and environmental changes with the use of Marketing Environmental, Social and 3.0, as well as stimulate the sale of products guaranteeing the financial viability of farmers and organizations, thus promoting the advancement of agroecology.